Comparative bio-efficacy test of insecticide aerosol against Culex quinquefasciatus - Hezian Jominit (2012)
A comparative bio-efficacy test of aerosol insecticides with three different formulations were evaluated against laboratory bred female adult of Culex quinquefasciatus mosquitoes in a simulated room conditions. The tested aerosol insecticides commercially sold in market as a household insecticide product. The insecticidal efficacy test was based in accordance with the WHO guideline for efficacy testing of household insecticide product (WHO/HTM/NTDPES/2009.3) and WHO guideline for safe and effective use of household insecticide product (WHO/CDS/WHOPES/99.1). The dosage mentioned on the label of each aerosol was used in the experiment. Tested aerosol insecticide formulations were coded as (A) Prallethrin 0.090% w/w + d-phenothrin 0.050%w/w, (B) d-transallethrin (75/25) 0.126% w/w + d-phenothrin 0.050%w/w, and (C) transfluthrin 0.040%w/w + cyfluthrin 0.025%w/w. Eight cages, each with 10 mosquuitoes were placed in different places of the room. Test mosquitoes were observed for knockdown at 5, 10, 15 and 20 minutes of exposure after applying the aerosol. The mortality rate was determined after 24 hours of holding period. The result showed the highest knockdown and mortality obtained from the aerosol formulation C, containing (transflutrin 0.040%w/w + cyfluthrin 0.025%w/w) while the lowest knockdown and mortality was found in the aerosol formulation B, containing (d-transallethrin (75/25) 0.126% w/w + d-phenothrin 0.050%w/w) which is significantly important.